A DESIGNING LOGO FOR WUDURI BEACH PEMALANG (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
Widuri Beach in Pemalang City was closed due to the corona virus pandemic and decrease the number of visitors. To increase that number, stakeholder must recalling people tough about tourism activity in Widuri Beach . There are various type of attractions, a natural beach, a swimming pool and cultural tours of the Sheikh's tomb. The author tries to positioning Widuri Beach as a Nature and Religion Tourism to target a new market. To achieve that, a new identity is needed to communicate new image of Widuri Beach with the right media. There are two categories of media, primary media in the form of billboards placed in strategic spots. And secondary media as digital and conventional in the form of poster, stand banner, brochure, ticket, and merchandises. The design process goes through several stages; pre-production, production and post-production. After completed all stages, a new logo was created and can be use in to branding processes.